High Performance Organic Electronic Devices Based on a Green Hybrid Dielectric. (21st August 2021) - Tousignant, Mathieu N.; Rice, Nicole A.; Niskanen, Jukka; Richard, Chloé M.; Ritaine, Dialia; Adronov, Alex; Lessard, Benoît H.
Abstract: As the cost of electronics decreases, the demand for short‐term and single‐use applications, such as smart packaging, increases. Consequently, there is significant need for electronically active biodegradable materials to reduce the environmental impact of disposable electronic devices. A bilayer dielectric is developed based on environmentally friendly, low‐cost solution‐processable polymers, fabricated by thermally crosslinking a toluene diisocyanate‐terminated polycaprolactone (TPCL) layer with the hydroxyl groups of a poly(vinyl alcohol)/cellulose nanocrystal (CNC) blended dielectric (PVAC ). Metal–insulator–metal (MIM) capacitors are fabricated and characterized under ambient and humid conditions. The incorporation of a TPCL layer in the bilayer dielectric results in a large reduction in moisture sensitivity when compared to neat PVAC without significantly altering the dielectric constant. When utilized as a dielectric in organic thin‐film transistors (OTFTs), the transistors prepared with the PVAC /TPCL dielectric have greater on/off ratios and hole mobilities, with reduced hysteresis compared to devices fabricated with PVAC . Furthermore, the fabricated OTFTs function at operating voltages six times lower when compared against a traditional silicon dioxide (SiO2 ) dielectric. The facile processing, combined with superior device performance, makes this green bilayer dielectric a promising candidate material for biodegradable disposable electronic applications. Abstract : The list of high performing biodegradable polymers dielectrics for electronics is short and often when selecting different materials their interaction or their processing is challenging. A new green polymer bilayer dielectric through interfacial crosslinking of two green polymers polycaprolactone (PCL) and poly(vinyl alcohol) (PVA) for use in single walled carbon nanotube (SWNT) based thin film transistors is reported.